Emotional vs. Rational Approach of Print Advertising: from the Swedish consumer's perspective - Johansson, Elin; Öberg, Lisa (2014)
Nowadays, marketers can choose between plenty of different marketing channels when reaching out to consumers. It is difficult for marketers to achieve successful advertisement due to all advertisements the world contains and because of more and more homogenous products. Also, consumers are being exposed to large amounts of advertisements and can easily choose not to pay attention to them, especially when it comes to printed ads, since they can choose whether to look at them or not. Marketers must find a way to create successful ads, and the approach can be either rational or emotional. There is an ongoing debate about which approach is the best, and the purpose of this study is to gain a better understanding on how consumers perceives rational versus emotional ads.This study is a qualitative study and six people have been interviewed around the city of Luleå. The purpose of this study is to help international advertisers gain a deeper understanding of the Swedish consumer’s perception, of both emotional and rational printed ads, by looking at how to capture their attention and how describe their attitudes toward the ad.Our main findings are that celebrities and sexual content generate a high level of attention from the viewers. Further, rational ads should include understandable and trustworthy information in order to receive positive attitudes from the consumer. The emotional ads received mixed and strong feelings, and generated attention. However, marketing managers need to be careful in order to not influence the consumer negatively. Validerat; 20140829 (global_studentproject_submitter)